2020
DOI: 10.1007/s12298-020-00848-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide association mapping of epi-cuticular wax genes in Sorghum bicolor

Abstract: Sorghum accumulates epi-cuticular wax (EW) in leaves, sheaths, and culms. EW reduces the transpirational and nontranspirational (nonstomatal) water loss and protects the plant from severe drought stress in addition to imparting resistance against insect pests. Results presented here are from the analysis of EW content of 387 diverse sorghum accessions and its genome-wide association study (GWAS). EW content in sorghum leaves ranged from 0.1 to 29.7 mg cm -2 with a mean value of 5.1 mg cm -2 . GWAS using 265,48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…We believe that this is the first report evaluating waxes in pea by GWAS. Greater lamina and petiole wax concentrations were associated with the stress environment, which is in agreement with several studies conducted on different crops species [ 14 , 16 , 45 , 46 ]. Abiotic stresses triggered increased wax concentrations as a stress-resistance response [ 12 , 47 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We believe that this is the first report evaluating waxes in pea by GWAS. Greater lamina and petiole wax concentrations were associated with the stress environment, which is in agreement with several studies conducted on different crops species [ 14 , 16 , 45 , 46 ]. Abiotic stresses triggered increased wax concentrations as a stress-resistance response [ 12 , 47 ].…”
Section: Discussionsupporting
confidence: 92%
“…ABC transporters are necessary for wax export from the site of synthesis to the outer membrane in plants [ 50 ]. Based on a GWAS study conducted on sorghum, Elango et al [ 16 ] reported several putative genes responsible for epicuticular-wax biosynthesis and export from the synthesis site to the outer plant membrane. Selecting genotypes for high epicuticular wax is essential in breeding stress-resistant crop cultivars for increased adaptation to environmental stresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, GLY-ASP-SER-LEU ESTERASE/LIPASE (GDSL lipase) is required for cutin polymerization in the developing cuticle ( Girard et al, 2012 ; Yeats and Rose, 2013 ), and the degree of pectin esterification is critical to cuticle structure by facilitating the diffusion of cutin precursors ( Bakan and Marion, 2017 ; Philippe et al, 2020 ). Transcription factors have also been identified to regulate various steps in cuticle development ( Borisjuk et al, 2014 ; Elango et al, 2020 ), but how these transcription factors, biosynthesis, and transport processes work together is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“… Mizuno et al (2013) reported that an ABC transporter gene, Sb06g023280 , is responsible for epi-cuticular wax biosynthesis in Sorghum. Elango et al (2020) assessed the epicuticular wax variability in the extensive genetic pool of Sorghum, and a genome-wide association mapping study showed genic regions associated with epicuticular wax production. Hence, the enhanced epicuticular wax content and the deposition of wax crystals on the leaf surfaces are essential components of plants for enhanced drought tolerance to overcome non-stomatal water loss.…”
Section: Discussionmentioning
confidence: 99%